2012
DOI: 10.1002/dneu.22060
|View full text |Cite
|
Sign up to set email alerts
|

Organization of myelin in the mouse somatosensory barrel cortex and the effects of sensory deprivation

Abstract: In rodents, the barrel cortex is a specialized area within the somatosensory cortex that processes signals from the mystacial whiskers. We investigated the normal development of myelination in the barrel cortex of mice, as well as the effects of sensory deprivation on this pattern. Deprivation was achieved by trimming the whiskers on one side of the face every other day from birth. In control mice, myelin was not present until postnatal day 14 and did not show prominence until postnatal day 30; adult levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 53 publications
6
49
0
Order By: Relevance
“…Not surprisingly, we performed immunostaining against the oligodendrocyte-specific molecule Olig2 [58,59,60] on sections of C57BL/6J brains with MLH and observed that oligodendrocytes are indeed present in MLH (data not shown). Moreover, as shown in figure 3d-f, ABA searches for oligodendrocyte-specific genes revealed the presence of cells expressing Mbp (18M; ABA 100082169), Plp1 (P28; ABA 100039826) and Gpr37 (P28; ABA 100039821) in heterotopia.…”
Section: Resultsmentioning
confidence: 99%
“…Not surprisingly, we performed immunostaining against the oligodendrocyte-specific molecule Olig2 [58,59,60] on sections of C57BL/6J brains with MLH and observed that oligodendrocytes are indeed present in MLH (data not shown). Moreover, as shown in figure 3d-f, ABA searches for oligodendrocyte-specific genes revealed the presence of cells expressing Mbp (18M; ABA 100082169), Plp1 (P28; ABA 100039826) and Gpr37 (P28; ABA 100039821) in heterotopia.…”
Section: Resultsmentioning
confidence: 99%
“…1d). Because the septal region is not obvious in the mouse brain (Petersen 2007), we combined the septal region with barrel walls and named the region the interbarrel septa/barrel wall according to a previous definition (Barrera et al 2013). The reconstruction results directly show that the penetrating vessels preferentially locate in the region of interbarrel septa/ barrel walls (Fig.…”
Section: Vectorization and Reconstruction Of Cells And Blood Vesselsmentioning
confidence: 98%
“…These findings would not result from connectivity between adjacent layer IV barrels (Feldmeyer, 2012) and, although there is evidence to suggest a higher concentration of myelin within the septal area compared to barrel hollows (Barrera et al, 2012), myelin is not essential for anisotropic diffusion in nerve fibres, with evidence of minor amounts of anisotropy in rodent and piglet cortex (Hoehn-Berlage et al, 1999;Mori et al, 2001;Thornton et al, 1997). In fact, anisotropy from un-myelinated nerves in garfish (Beaulieu and Allen, 1994), rodent (Seo et al, 1999), zebrafish (Ullmann et al, 2013) and human fetal brain (Tucciarone et al, 2009) suggest the radial alignment of microstructure including cell membranes is a sufficient barrier to diffusion to result in anisotropic diffusivity.…”
Section: Thalamo-cortical Connectivitymentioning
confidence: 98%
“…The structural composition and connectivity of the "whisker pathways" has been described using 2D histologic and functional activation methods. Network tracking techniques include lesion studies, (Killackey and Fleming, 1985;Killackey and Leshin, 1975); carbocyanine dyes (1,1'-dioctadecyl-3,3,3',3'-tetramethylindocarbocyanine Perchlorate; DiI, DiA) (Kivrak and Erzurumlu, 2013;Seehaus et al, 2013) and myelin staining (Barrera et al, 2012); these techniques are also complemented by Lenti and Adeno-associated viral vector expression of fluorescent proteins (Aronoff et al, 2010;Dittgen et al, 2004;Wimmer et al, 2010). A range of macroscopic to microscopic functional connectivity mapping techniques include functional MRI (Kim et al, 2012;Yang et al, 1996), 2-photon imaging of electrical activity using voltage-sensitive dyes (Petersen et al, 2003a;Petersen et al, 2003b) and channelrhodopsins to map neuronal connectivity have also been conducted (Paz et al, 2011;Petreanu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%